ChemInform Abstract: Reversible Sodiation in Maricite NaMn1/3Co1/3Ni1/3PO4 for Renewable Energy Storage. Issue 18 (11th April 2013) - Minakshi, Manickam; Meyrick, Danielle
Abstract Single‐phase, high‐purity NaMn1/3Co1/3Ni1/3PO4 of the orthorhombic maricite mineral type is prepared by sol‐gel and combustion routes starting with stoichiometric mixtures of NaOAc, Mn(OAc)2, Co(OAc)2, Ni(OAc)2, NH4H2PO4, and for sol‐gel processing citric acid or PVP as chelating agent, (80°C, pH 3.5, 1.